Left atrial appendage occlusion: a better alternative to anticoagulation? - Akın, Ibrahim; Nienaber, Christoph (World journal of cardiology, 2017)
Non-valvular atrial fibrillation is associated with a significantly increased risk of embolic stroke due to blood clot forming predominantly in the left atrial appendage (LAA). Preventive measures to avoid embolic events are permanent administration of anticoagulants or surgical closure of the LAA. Various clinical trials provide evidence about safety, effectiveness and therapeutic success of LAA occlusion using various cardiac occluder devices. The use of such implants for interventional closure of the LAA is likely to become a valuable alternative for stroke prevention, especially in patients with contraindication for oral anticoagulation as safety, clinical benefit and cost-effectiveness of LAA occlusion has recently been demonstrated.
Gesehen am 11.04.2018